2016
DOI: 10.4292/wjgpt.v7.i1.78
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of functional symptoms in inflammatory bowel disease in remission

Abstract: it in the present work. We describe a problematic that comprises physiopathological uncertainties, diagnostic difficulties, as IBS-like symptoms are very similar to those produced by an inflammatory flare, and the necessity of appropriate management of these patients, who, although in remission, have impaired quality of life. Ultimately, from almost a philosophical point of view, the presence of IBS-like symptoms in IBD patients in remission supposes a challenge to the traditional functional-organic dichotomy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 121 publications
(214 reference statements)
0
30
0
1
Order By: Relevance
“…Finally, we excluded any study that exclusively used patient‐reported symptoms to quantify disease activity, for example, survey‐based studies. This was to minimise the potential confounding from gastrointestinal symptoms originating from co‐existing functional bowel disorders that can occur in the absence of active intestinal inflammation . This did not eliminate certain commonly used clinical scoring systems such as the CDAI that contain a component of patient‐reported symptoms in the score.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we excluded any study that exclusively used patient‐reported symptoms to quantify disease activity, for example, survey‐based studies. This was to minimise the potential confounding from gastrointestinal symptoms originating from co‐existing functional bowel disorders that can occur in the absence of active intestinal inflammation . This did not eliminate certain commonly used clinical scoring systems such as the CDAI that contain a component of patient‐reported symptoms in the score.…”
Section: Methodsmentioning
confidence: 99%
“…Repeated exposure to psychological stress indeed can trigger the onset of IBS and exacerbate pre‐existing IBS symptoms . In preclinical models, acute intestinal inflammation, as in ulcerative colitis (UC) patients, leads to VHS, not only during acute flares of inflammation but also persisting after resolution of the inflammatory response …”
Section: Introductionmentioning
confidence: 99%
“…5 In preclinical models, acute intestinal inflammation, as in ulcerative colitis (UC) patients, leads to VHS, not only during acute flares of inflammation but also persisting after resolution of the inflammatory response. [6][7][8][9] It is well recognized that VHS in IBS and UC patients in remission can result from increased activation and/or sensitization of afferent nerve terminals via the release of bioactive mediators such as histamine, serotonin, proteases, and cytokines. [10][11][12][13][14] However, although less well studied, VHS can also result from altered pain signaling at the level of spinal cord.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, overlaps have also been observed between these diseases with regard to clinical symptoms [15]. Notably, IBS-like symptoms are often found in UC patients who have no evidence of the ongoing clinical disease activity [6,8,16]. Numerous studies have demonstrated possible mechanisms related to the development of IBS-like symptoms in quiescent UC patients [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%